Study of mortality rate following fixation of proximal femur fractures by gamma nail - Fadel, Mohie Eldin; Rafalla, Awad E.; Abbadi, Albraa Ahmed; Alaaeldin, Ahmed (International Journal of Research in Orthopaedics, 2026)
Background: Proximal femur fractures, are prevalent in elderly individuals due to osteoporosis. These fractures are significant causes of morbidity and mortality worldwide. Surgical treatment typically involves fixation techniques like the gamma nail, a cephalomedullary implant designed to provide stable fixation with minimal soft-tissue trauma. However, despite these advancements, the mortality rates post-surgery remains high, with early mortality reaching 7-10% and one-year mortality between 20-30%. Identifying risk factors for mortality in patients undergoing gamma nail fixation is crucial to improve patient outcomes and guide surgical decision-making. The primary aim of the study was to evaluate the mortality rate following Gamma Nail fixation for proximal femur fractures in elderly patients at Elhadra University Hospital. The study sought to correlate various preoperative factors, including age, comorbidities, and mobility scores, with mortality outcomes to better predict patient prognosis. Methods: This retrospective study included 220 patients aged 60 years or older who underwent Gamma Nail fixation for proximal femur fractures at Elhadra University Hospital between January 2023 and January 2024. Exclusion criteria were polytrauma patients and those younger than 60 years. Data collected included patient demographics (age, sex), preoperative medical history (comorbidities, previous surgeries, drug use), and functional status assessed using the Parker mobility score. The American society of anesthesiologists (ASA) classification and Nottingham hip fracture score (NHFS) were also recorded. Postoperative complications, including co-morbidities, intensive care unit (ICU) admissions, and mortality rates (both within 30 days and one year), were analyzed. Results: The mean age of the patients was 70.98 years, with a slight majority being female (53.64%). Intertrochanteric fractures were the most common (85%), followed by subtrochanteric fractures (15%). Preoperative activity levels varied, with the majority reporting moderate activity. Cardiovascular diseases were the most prevalent comorbidity, affecting 66.33% of patients. Mortality rates were high, with 30.45% of patients dying during the study period, 8.64% of whom died within the first month. The study found that advanced age, higher ASA scores, low mobility scores, and cardiovascular comorbidities significantly correlated with higher mortality rates. Additionally, patients with higher NHFS scores (≥5) and those requiring postoperative ICU care had a significantly higher mortality risk. Conclusions: The study concluded that gamma nail fixation is effective for treating proximal femur fractures in elderly patients, but mortality remains high, particularly in patients with advanced age, poor preoperative functional status, and significant comorbidities such as cardiovascular diseases. The identification of high-risk patients using tools like the ASA score, NHFS, and Parker mobility score can help guide perioperative management and improve patient care. Postoperative complications, including ICU admissions, were also strongly associated with increased mortality. Further research focusing on risk factor modification and enhanced perioperative care is essential to reduce mortality in this vulnerable patient population.